A lesson for post-COVID healthcare: assessment of physical and psychosocial risk factors on perceived pain intensity among urban individuals - Ho, Hung Chak; Bai, Wentao; Wong, Stanley Sau-Ching; Cheung, Chi Wai (Frontiers in Psychology, 2025)
BackgroundPerceived pain intensity is an important determinant of health-related quality of life. A lack of studies has investigated the co-influences of physical and psychosocial risk factors on perceived pain intensity and the shifts in effects after pandemic. As a post-COVID symptom, it is important to re-assess the risk factors for post-COVID heath care.MethodsFour dimensions of physical/psychosocial risk factors were assessed: medical history, personal wellbeing and psychological distress, lifestyle, and socio-demographic characteristics. We first identified subgroups with significant increase in perceived pain intensity after pandemic by a comparison with the baseline group (all participants). Based on the variables associated with a severe increase in pain score (NRS), multivariate regression models were applied to identify risk factors on perceived pain intensity.ResultsAmong 3,237 urban individuals in Hong Kong, 20.95 and 30.58% were with severe pain (NRS > = 4) before and after pandemic. Participants with respiratory disease had the most significant increase in perceived pain intensity (increase in NRS: 1.29 [0.65, 1.93]), seconded by those with known psychiatric diseases and living with special needs. After pandemic, insomnia, known psychiatric diseases, female, and low household income remained as significant risk factors, and insomnia remained as the most significant (estimate: 1.018 [CI: 0.814, 1.221]). The effect sizes of these factors were increased after pandemic. Respiratory disease, cardiovascular disease, and low education (secondary school or below) were additional risk factors.ConclusionIt is necessary to develop up-to-date interventions targeting vulnerable populations, particularly individuals with known psychiatric diseases and insomnia, for pain reduction.